Perspectives for Researching British Appeasement of Nazi Germany in the Inter-War Years Using the Digitized Newspaper Collections of the British Library - Vasiliu, Andrei (Revista Hiperboreea, 2017)
This paper aims to verify that the methods for researching the British appeasementpolicy towards Germany in the inter-war years can include the new method of studying the digitizedcollections of newspapers of the British Library. The policy of appeasement led by Great Britainduring the inter-war years still represents a very attractive subject of research. The challenge lies notonly in the new data harvested from primary sources such as documents and newspapers but also inthe new methods of researching that may be applied, and that may increase the interest of scholars. Today, researching the digitized collections of archives are not even a futuristic resource, but a growingnecessity. Accessing the British Library's digitized collections through the British Newspaper Archivewebsite is often easier and more efficient than going to the archives. The site has more than 40 milliondigitized newspapers, mainly local periodicals, which can be accessed by searching for keywords,establishing filters and saving results to retrieve them later. The electronic resources of the digitizedcollections provide valuable help in my doctoral research on the Anglo-French appeasement reflectedin the newspapers, which proves to be a great challenge, given the fact that the subject was widelycovered in many of the central newspapers. But, of course, this method immediately poses multiplequestions: is this method of research as rigorous as the traditional research conducted in the archives?Does this method provide the intercoder reliability framework required for such works? These are theresearch questions that remain at the center of this article. Previous research on the subject of digitizedcollections and also the analysis of the resources of the British Newspaper Archive in comparison withthe traditional British Library resources can provide an answer.